Doppler interrogation of fetoplacental circulation in hypertensive disorder of pregnancy and their perinatal outcomes - Devi, Jyoti; Kumar, Devender; Shukla, Mala; Jain, P. K. (International Journal of Research in Medical Sciences, 2017)
Background: Hypertensive disorders of pregnancy are one of the major causes of maternal morbidity-mortality leading to 10-15% of maternal deaths especially in developing areas of the world. The Doppler examination makes it possible by providing a unique, non-invasive and safe method of studying blood flow characteristics in both the fetoplacental and uteroplacental circulations that is being used in clinical evaluation of high risk pregnancies. The aim was to study early detection of fetoplacental compromise in hypertensive disorder of pregnancy with Doppler indices and to know its role in predicting perinatal outcomes and interventional strategies in these patients. Methods: This prospective study was conducted on 100 subjects, 50 patients in study group with hypertensive disorders and 50 patients in control group with normotensive pregnancy. Doppler studies of umbilical and middle cerebral artery done and parameters recorded were systolic/diastolic ratio, pulsatility index and resistance index at 28-37 weeks of gestation. Perinatal outcomes of both groups compared, analyzed statistically. Multiple pregnancy, chronic hypertension, fetal congenital anomalies, systemic disease and those lost to follow up till delivery were excluded from study. Results: Statistically significant difference in the incidence of induction of labour (p=0.012) and caesarean delivery (p=0.049), preterm delivery (p=0.004), low birth weight (p=0.003), low apgar score (p=0.045) and NICU admission in the patients with abnormal umbilical artery doppler of hypertensive group were seen .66.66% and 100% perinatal mortality seen in absent end diastolic flow and reverse end diastolic flow of umbilical artery in hypertensive group respectively. Conclusions: Abnormal umbilical artery had highest sensitivity 76% and positive predictive value 84% in predicting adverse perinatal outcome and MCA Doppler having highest specificity 96% to exclude the false positive results of abnormal UA. The sequential study of both vessels useful in predicting interventional strategies and improving perinatal outcomes.